Effect Applying Digital Technology and Entrepreneurial Orientation Against Performance MSMEs (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the effect of synergy between the application of digital technology and entrepreneurial orientation on the performance of MSMEs coffee shop in Bojonegoro. The results of the analysis showed that the combination of these two variables significantly improved business performance, exceeding the individual impact of each variable. These findings underline the importance of a holistic approach in the development of MSMEs in the digital age, which combines technological innovation with. entrepreneurial spirit. The use of technology such as online ordering applications, inventory systems, and data analysis allows coffee shop SMEs to operate more efficiently, save time and costs, and reduce errors. This research provides important implications for the government and related stakeholders to design policies that support the adoption of digital technology by MSMEs such as technology service providers, business consultants, and the entrepreneur community can accelerate the digital transformation process. as well as a more targeted entrepreneurial capacity building program.